2020
DOI: 10.1002/rcm.8580
|View full text |Cite
|
Sign up to set email alerts
|

Analytically validated protein biomarkers of chronic pancreatitis and pancreatic cancer for potential clinical diagnosis with mass spectrometry

Abstract: Rationale Chronic pancreatitis (CP) is a pancreatic disease with poor prognosis and pancreatic cancer (PC) is one of the most lethal types of cancer that is symptomless in the early stage. Because the clinical and image findings of CP can overlap that of pancreatic cancer (PC) which leads to confusion in the diagnosis and treatment of PC, discovery/verification/validation of more accurate protein biomarkers to diagnose CP and PC is in urgent need. Methods The PubMed, Web of Science, and Google Scholar were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…28 29 Those biomarkers analytically validated for diagnosis using mass spectrometry are reviewed by Chou et al, but diagnostic accuracy is mostly unknown. 30 Studies in rodents employing spontaneous and pharmacologically induced models of CP suggested significant alterations to the pancreatic metabolome, including energy production, anabolism, lipid synthesis and ROS detoxification pathways. 31 32 Small and due to their heterogeneity inconclusive nuclear MR-spectroscopy-based human studies identified changes in citrate and adenosine levels in urine and 33 34 This prompted us to conduct a trial with a study design more adequate for biomarker development.…”
Section: Discussionmentioning
confidence: 99%
“…28 29 Those biomarkers analytically validated for diagnosis using mass spectrometry are reviewed by Chou et al, but diagnostic accuracy is mostly unknown. 30 Studies in rodents employing spontaneous and pharmacologically induced models of CP suggested significant alterations to the pancreatic metabolome, including energy production, anabolism, lipid synthesis and ROS detoxification pathways. 31 32 Small and due to their heterogeneity inconclusive nuclear MR-spectroscopy-based human studies identified changes in citrate and adenosine levels in urine and 33 34 This prompted us to conduct a trial with a study design more adequate for biomarker development.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the development work has focused on MS instrumentation and techniques. Additionally, developments in liquid chromatography (LC) have enabled complex mixture analysis. This has led to the wide-scale adoption of LC-MS techniques by the scientific community for the study of human disease. Indeed, LC-MS ‘omics methods have been broadly utilized to investigate conditions such as cardiovascular disease, cancer, diabetes, , and neurodegenerative disorders. …”
Section: Introductionmentioning
confidence: 99%
“…Direct markers of pancreatic exocrine function are invasive because they involve obtaining pancreatic juices via endoscopy or Dreiling tube following stimulation by secretin or cholecystokinin. Bicarbonate, lipase, or trypsin is then measured, and these measurements are highly sensitive for late CP but have a lower sensitivity range of 70-75% for early chronic pancreatitis [25]. Indirect markers, on the other hand, are non-invasive tests of pancreatic insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect markers, on the other hand, are non-invasive tests of pancreatic insufficiency. One example is faecal elastase-1, with a cutoff of 100 micrograms having a sensitivity of 46.5% and a specificity of 88% for the diagnosis of CP [25]. Early biomarkers for CP include chemokines like transforming growth factor-Beta 1 (TGF-β1), platelet-derived growth factor BB, and chemerin, which are elevated in CP [25].…”
Section: Discussionmentioning
confidence: 99%